Four-year residual impacts of single biochar application on soil fertility and microbial community structure in aeolian sandy soils of semi-arid Inner Mongolia - Zhou, Lei; Chu, Junqi; Zhang, Yufen; Wang, Qi; Liu, Yanting; Zhao, Baoping (Frontiers in Microbiology, 2025)
Biochar (BC) application is widely recognized as a promising strategy for enhancing soil fertility; however, its lasting effects on microbial communities in aeolian sandy soils of semi-arid regions remain poorly understood. To fill this knowledge gap, we conducted a field experiment to evaluate long-term changes in soil properties and microbial community structure in a buckwheat cropping system, 4 years after a single application of biochar (BC) at rates of 0 (BC0), 20 (BC1), 40 (BC2), and 60 (BC3) Mg ha−1 in aeolian sandy soils of Inner Mongolia, China. Results revealed significant improvements in soil pH, moisture content, organic carbon (SOC), and available nutrients, as well as microbial biomass and enzyme activity, particularly at higher BC application rates (BC2 and BC3). SOC increased by 9.42% (BC2) and 14.13% (BC3). BC application altered microbial community composition, with minimal effects on bacterial diversity but reduced fungal diversity. Enhanced soil C and N cycling was linked to shifts in key microbial genera, while relative abundances of potential pathogens such as Fusarium and Nothophoma declined by up to 58 and 77%, respectively. Mantel tests confirmed significant correlations between shifts in microbial diversity and community composition and changes in soil properties, with particularly strong associations for fungal diversity related to SOC (r = 0.50, p < 0.001) and microbial biomass carbon (SMC; r = 0.43, p < 0.001). Redundancy analysis further revealed that bacterial communities were significantly associated (p < 0.05) with pH, microbial biomass nitrogen (SMN), and invertase activity, while fungal communities were linked to pH, microbial biomass phosphorus (SMP), and urease activity. This study underscores the potential of biochar to enhance soil health by improving soil fertility, reshaping microbial community composition, and suppressing soil-borne pathogens, particularly at higher application rates. These findings provide valuable insights for the reclamation of degraded sandy soils in semi-arid regions on a global scale.